A retrospect and outlook on the neuroprotective effects of anesthetics in the era of endovascular therapy - Zhang, Tianhao; Deng, Daling; Huang, Shiqian; Fu, Daan; Wang, Tingting; Xu, Feng; Ma, Lulin; Ding, Yuanyuan; Wang, Kaixin; Wang, Yafeng; Zhao, Wenjing; Chen, Xiangdong (Frontiers in Neuroscience, 2023)
More than half a century ago, studies on the neuroprotection of anesthetics were already carried out. Subsequently, many cell and animal experiments verified it. However, when it comes to clinical trials, the neuroprotective effect of anesthetics was not clearly observed. These contradictory results suggest the mismatch between basic research and clinical trials. The Stroke Therapy Academic Industry Roundtable X proposed that the emergence of endovascular thrombectomy (EVT) would provide a proper platform to verify the neuroprotective effect because the hemodynamics of EVT patients is very close to the ischemia-reperfusion model in basic research. With the widespread use of EVT, it is necessary for us to re-examine the neuroprotective effects of anesthetics to guide the use of anesthetics during EVT because the choice of anaesthesia is still based on team experience without a definite guideline. In this paper, we described the research status of anaesthesia in EVT and summarized the neuroprotective mechanisms of some anesthetics. And then we focused on the contradictory results between clinical trials and basic research and discussed its causes. Finally, we conducted an outlook on the neuroprotection of anesthetics in the era of endovascular therapy.